POLA KOMUNIKASI ANTARPRIBADI PELATIH DALAM MENINGKATKAN SKILL PEMAIN BASKET PEMULA - Manogari, Rialdo Rezeky; Manafe, Mario Galilea Hendrian (JURNAL PUSTAKA KOMUNIKASI, 2019)
This study aims to determine the interpersonal communication patterns used by trainers in improving the skills of beginner basketball players in the community of 3 World Handles and to introduce techniques and terms in playing basketball through verbal and nonverbal communication to novice basketball players. In this study the theory used is Interpersonal Communication Theory and Competency Theory according to Spencer & Spencer in 2007. This research uses data collection techniques using interviews and literature. The methodology of this research is a qualitative descriptive approach about a social phenomenon and case study. Based on the results of the study, it was shown that in the pattern of interpersonal communication of the trainers in the basketball community 3 World Handles were good and effective towards the players, especially beginner players and also in providing motivation to the players and teams.